Reaching out to industry and community - New Sunday Times,; Suzieana Uda Nagu, (2007)
ACADEMICS from Malaysia's four research universities - Universiti of Malaya (UM), Universiti Kebangsaan Malaysia (UKM), Universiti Putra Malaysia (UPM) and Universiti Sains Malaysia (USM) - recently received their appointment letters for the positions of deputy vice chancellors of new portfolios.